The social dimensions of adjustment in Africa : a policy agenda (World Bank, 1990)
This is study by the staff of the SDA unit at the World Bank, and the judgments in it do not necessarily reflect the views of the board of executive directors or the governments they represent. The material in this publication is copyrighted.